Urban-rural differences for health promotion in faith-based organizations - Melissa Bopp; Benjamin L Webb; Elizabeth A Fallon (Rural Nurse Organization; Binghamton University, 2012)
Background: Rural faith-based organizations (FBO) serve an important social, cultural and political role in their communities, but compared to their urban counterparts, less is known about their ability to deliver health and wellness activities (HWA). This study's purpose was to examine differences in factors related to HWA between urban and rural FBOs. Methods: A convenience sample of faith-leaders (N = 824) completed an online survey assessing faith leader demographics (age, sex, education, body mass index, race), FBO demographics (denomination, location), types of HWA, and barriers to HWA. Results: Respondents were primarily White (93%), male (72%), middle aged (53.2+ 12.1 yrs), with Methodist (42.5%) or Lutheran (20.2%) affiliations. Compared to urban faith leaders (n=599), rural faith leaders (n=225) reported lower physical activity levels and higher rates of overweight (p's<0.05). Compared to urban FBOs, rural FBOs were more likely to report offering no HWA (χ2=3.00, df=1, p=0.04), and rural FBOs offered fewer HWA (3.73±2.89) than urban FBOs (4.98±3.25; t=4.92, df=781, p<0.001). Urban FBOs offered more educational health classes, health fairs, health screenings, and physical activity/sports groups compared with rural FBOs (ps<0.05). Rural FBOs were more likely to report a lack of congregational interest and lack of lay leadership as barriers to HWA, whereas urban FBOs indicated that other FBO activities conflicted with HWA (ps<0.05). Conclusions: This study revealed important differences in factors related to HWA in urban and rural areas. This study provides public health professionals with insight regarding implementation of HWA in rural and urban FBOs.